Transcriptional and Catalytic Responsiveness of the Antarctic Fish Trematomus bernacchii Antioxidant System toward Multiple Stressors - Maria Elisa Giuliani; Alessandro Nardi; Marta Di Carlo; Maura Benedetti; Francesco Regoli (Antioxidants, 2021)
Ocean-warming and acidification jeopardize Antarctic marine species, adapted to cold and constant conditions and naturally exposed to high pro-oxidant pressures and cadmium (Cd) bioavailability. The aim of this study was to investigate if projected temperature increase and pH reduction may affect the accumulation and the effects of Cd in the rockcod Trematomus bernacchii. Organisms were exposed for 14 days to six scenarios, combining environmental or increased temperature (−1 °C, +1 °C) and control or reduced pH (8.05, 7.60), either with or without Cd (40 µg/L). Responses in liver and gills were analyzed at different levels, including mRNA and functional measurements of metallothioneins and of a wide battery of antioxidants, integrated with the evaluation of the total antioxidant capacity and onset of oxidative damages. In the gills, metallothioneins and mRNA of antioxidant genes (nrf2, keap1, cat, gpx1) increased after Cd exposure, but such effects were softened by warming and acidification. Antioxidants showed slighter variations at the enzymatic level, while Cd caused glutathione increase under warming and acidified scenarios. In the liver, due to higher basal antioxidant protection, limited effects were observed. Genotoxic damage increased under the combined stressors scenario. Overall results highlighted the modulation of the oxidative stress response to Cd by multiple stressors, suggesting the vulnerability of T. bernacchii under predicted ocean change scenarios.